2002
DOI: 10.1089/153623002320253283
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Method for Porcine Cloning by Nuclear Transfer Using In Vitro-Matured Oocytes

Abstract: To date, the efficiency of pig cloning by nuclear transfer of somatic cell nuclei has been extremely low, with less than 1% of transferred embryos surviving to term. Even the utilization of complex procedures such as two rounds of nuclear transfer has not resulted in greater overall efficiencies. As a result, the applicability of the technology for the generation of transgenic and cloned animals has not moved forward rapidly. We report here a simple nuclear transfer protocol, utilizing commercially available i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(104 citation statements)
references
References 13 publications
(24 reference statements)
2
99
1
Order By: Relevance
“…We and authors of another study reported that phenotypic instability in swine resulted from scNT Archer et al, 2003;Park et al, 2004Park et al, , 2005. However, other groups have observed few problems (Betthauser et al, 2000;De Sousa et al, 2002;Walker et al, 2002;Yin et al, 2002). In cattle, the donor cell type was found to be responsible for some of the abnormal phenotypes that were observed, as cells derived from adults resulted in more abnormalities (Heyman et al, 2002).…”
Section: Discussionmentioning
confidence: 80%
“…We and authors of another study reported that phenotypic instability in swine resulted from scNT Archer et al, 2003;Park et al, 2004Park et al, , 2005. However, other groups have observed few problems (Betthauser et al, 2000;De Sousa et al, 2002;Walker et al, 2002;Yin et al, 2002). In cattle, the donor cell type was found to be responsible for some of the abnormal phenotypes that were observed, as cells derived from adults resulted in more abnormalities (Heyman et al, 2002).…”
Section: Discussionmentioning
confidence: 80%
“…Since the first cloned pigs were generated using somatic cell cloning [4], substantial improvement for this technique has been realized [5,6]. However, the efficiency of pig cloning has been lower than that of other domestic animals, with only 1%-5% of the embryos reconstructed by nuclear transfer surviving to term [7,8]. Apoptosis, a type of programmed cell death, is a physiological process occurring spontaneously during normal preimplantation embryo development [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear transfer was performed by Viagen, Inc. (Austin, TX) as previously described (65). Briefly, ATM-targeted PFF were collected in salt-buffered NCSU-23 containing 10% fetal calf serum and transferred into the oocytes.…”
Section: Nuclear Transfermentioning
confidence: 99%